The parental effects of body size on developmental phenotype in Harmonia axyridis. Issue 6 (11th December 2020) - Michaud, J.P.; Bayoumy, M.H.; Perumal, R.; Awadalla, S.S.; El-Gendy, M.; Abdelwahab, A.H.
Abstract: Body size is a trait with many potential impacts on fitness. Adult body size can affect the strength of condition-dependent parental effects that determine offspring phenotypes, with potentially important transgenerational consequences. In a preliminary experiment, larval food deprivation (30 min daily access) created Harmonia axyridis Pallas (Coleoptera: Coccinellidae) females that weighed <50% of controls reared on ad libitum food (eggs of Ephestia kuehniella Zeller). Although only 1/3 of larvae survived to adulthood in the 30 min treatment, adult pairs produced eggs that were not significantly different in size from those of pairs fed ad libitum as larvae. Less extreme larval food deprivation (4 h daily access) was used to create a cohort of H. axyridis that weighed <60% of controls reared on ad libitum food. Small couples had lower 20-day fecundities and reduced egg fertility relative to large couples. Both egg and pupal periods were shortest when both parents were small, and longest when both parents were large, with reciprocal crosses intermediate. There were no consistent effects of parental body size on larval development time, but the progeny of small females mated to large males pupated later than other treatments. Progeny of large pairs had the heaviest adult weights at emergence, and progeny of small pairs, the lightest, with the progeny of reciprocal crosses intermediate. Small females produced the lightest female offspring, whereas small males sired the lightest male offspring, suggesting stronger responses to epigenetic signals from parents of the same sex. These results indicate that H. axyridis cohorts maturing with abundant food will produce progeny with larger potential body size and fitness, whereas those experiencing food limitation will confer size and fitness limitations to the subsequent generation, with potentially important implications for short-term population dynamics.